An analysis on the impact of internal recruitment on local authorities performance in Zimbabwe : the case of Gweru City Council - Maruba, Loreen (Midlands State University, 2020)
The research investigated the Impact of Internal Recruitment on Local Authorities focusing on Gweru City Council. The study used a descriptive research design and the quantitative research approach. A sample of 12 managers, 23 members of technical staff and 42 shop floors was used. Primary data was collected using questionnaires. The research investigated the methods of internal recruitment, impact of internal recruitment, challenges and the strategies for mitigating the challenges. The research found that council employees were notified of available vacancies through notice boards, magazines and by managers and supervisors. The council website was not used. Available vacancies in the council were filled through promotions, transfers from other department and job referrals to fill in available vacancies. The study showed that internal recruitment managed to ensure that workers recruited from within the existing council labour force fit well with the council culture. Internal recruitment assisted the council in retaining qualified personnel as it acted as a reward and recognition to the employees. It saved production time and assisted the council in reducing recruitment coasts. However, the study also found that internal recruitment inhibited innovation as it promoted stagnation and was associated with favouritism and lacked transparency. It also revealed that internal recruitment led to hiring of less qualified staff. The research further revealed that the internal recruitment process suffered from management influence and the use of inappropriate job descriptions and person specifications. To mitigate the challenges the study found out that there was the need for the council to train the internal recruiters or to outsource the recruitment function to an independent authority. The study also found out that there was the need to involve supervisors in the internal recruitment process. The research recommended that the Gweru City Council recruitment authorities be trained in recruitment skills and competencies and appropriate job descriptions and person specifications were to be used during the internal recruitment process. It further recommended that the recruitment function be outsourced to experts and supervisors were to be involved in the internal recruitment process. There was also the need for management to stop interfering with the internal recruitment process.